2019
DOI: 10.1002/jcb.29237
|View full text |Cite
|
Sign up to set email alerts
|

miR‐200a mediates protection of thymosin β‐4 in cardiac microvascular endothelial cells as a novel mechanism under hypoxia‐reoxygenation injury

Abstract: Thymosin β‐4 (Tβ4) is a ubiquitous protein, which has been suggested to regulate multiple cell signal pathways and a variety of cellular functions. However, the role Tβ4 plays in the cardiac microvascular endothelial cells (CMECs) under myocardial ischemia/reperfusion injury is currently unknown. Here we investigated the effects of Tβ4 on hypoxia/reoxygenation (H/R) induced CMECs injury and its potential molecular mechanism. Cultured CMECs were positively identified by flow cytometry using antibody against CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The miR-200a mediates the ameliorative impact of thymosin -4 (T-4) in cardiac microvascular endothelial cells after hypoxia-reoxygenation injury (Li et al , 2017). T-4 exerts a stimulatory effect on the expression of miR-200a.…”
Section: Mir-200amentioning
confidence: 99%
“…The miR-200a mediates the ameliorative impact of thymosin -4 (T-4) in cardiac microvascular endothelial cells after hypoxia-reoxygenation injury (Li et al , 2017). T-4 exerts a stimulatory effect on the expression of miR-200a.…”
Section: Mir-200amentioning
confidence: 99%
“…Moreover, miR-200a mediated the proliferation of hepatic stellate cells and development of fibrosis by targeting the 3′-UTR of SIRT1 via the SIRT1/Notch signal pathway [12]. It was also involved in protecting thymosin β-4 in cardiac microvascular endothelial cells following hypoxia/reoxygenation injury via the NRF2 antioxidant pathway [13]. Moreover, expression of miR-200a was downregulated in fibrostenosing Crohn's disease [14], HBV-induced hepatocellular carcinoma [15] and human glioma [16], thereby highlighting its function as a suppressor of many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that miR-200a inhibited HCC cell proliferation,27282930 and that it plays an important role in protecting cardiomyocyte survival under hypoxic conditions. Li, et al31 pointed that miR-200a level was decreased in H/R-cardiac microvascular endothelial cells (CMECs), and thymosin beta 4 attenuated hypoxia-reoxygenation induced CMECs injury by miR-200a-Nrf2 signaling. Sun, et al32 manifested that miR-200a was significantly downregulated in ischemic myocardial tissues and hypoxic cardiomyocytes, and suppression of Keap1 by miR-200a exerted cardioprotective effect against hypoxia-induced oxidative stress and cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%